Pemberdayaan Ekonomi Masyarakat Melalui Pemanfaatan Lahan Perkarangan Rumah - Sinollah; Kiki Wardani Lutfiyah; M Tody Arsyianto (Jurnal Pengabdian Masyarakat: Tipis Wiring, 2022)
Desa Palaan has natural and cultural wealth that is still preserved for agricultural areas and garden development, this service activity is expected to play a role and participate actively in the community. The purpose of its implementation is to establish, foster, and develop the potential that exists in the village, as community empowerment, through the use of local potential to lift the community from the poverty line. In general, the potential possessed by Desa Palaan is quite large, especially in terms of developing agriculture and plantations. With natural conditions and physical potential in agriculture, this village is a medium-land area that has very fertile soil conditions. By utilizing home yard land as an economic empowerment for the Desa Palaan community through pineapple cultivation, the future direction of Desa Palaan is to become a Pilot Inkubasi Inovasi Desa Pengembangan Ekonomi Lokal (PIID-PEL), to continue to innovate in an effort to improve the economy in the village through pineapple cultivation which some have pioneered by society